Why Jephthah's Daughter Weeps : A Child-Oriented Interpretation - Talbot, Margaret Murray (Biblical Interpretation Series, 2022)
Why does Jephthah's daughter weep? Readers have creatively imagined the causes of her tears as she weeps upon her betulim -usually translated virginity or maidenhood. But her menstrual cycle's relation to these terms is rarely mentioned. A child-oriented theoretical and methodological foundation and research with post-menarcheal girls provide new answers to oft-raised questions about Bat-Yiphtach's weeping and her agency. Through an in-depth philological review and a focus on the "excluded middle" of the child-adult binary, this translation and interpretation of the story contribute to the field of childhood studies and shows that menarche and menstruation play a larger role in the narrative than readers have realized.